2008
DOI: 10.1108/17539260810891488
|View full text |Cite
|
Sign up to set email alerts
|

The capital structure determinants of REITs. Is it a peculiar industry?

Abstract: PurposeUnlike previous studies on capital structure decisions, the purpose of this paper is to focus on US real estate investment trusts (REITs) in order to find out the main determinants of capital structure choice for real estate companies and in order to verify if they are related to factors similar to those affecting the decisions of public firms in other sectors.Design/methodology/approachUsing a methodology similar to Rajan and Zingales, a sample of 119 listed REITs with different investment strategies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 100 publications
7
46
1
4
Order By: Relevance
“…Earnings volatility or operating risk has mainly has a negative impact upon the debt ratio, supporting Trade-off Theory. Amongst numerous others, Booth et al (2001), Morri and Beretta (2008), and Chikolwa (2009) have found this result, whereas Wiwattanakantang (1999) found mixed results.…”
Section: Empirical Findings Of Capital Structure Determinants Used Inmentioning
confidence: 69%
“…Earnings volatility or operating risk has mainly has a negative impact upon the debt ratio, supporting Trade-off Theory. Amongst numerous others, Booth et al (2001), Morri and Beretta (2008), and Chikolwa (2009) have found this result, whereas Wiwattanakantang (1999) found mixed results.…”
Section: Empirical Findings Of Capital Structure Determinants Used Inmentioning
confidence: 69%
“…Research has demonstrated that capital structure choice varies significantly across industries (Morri and Beretta, 2008;Feng et al, 2007). Property industry is unique in different industries in terms of capital structure choice, because property companies have more collateral (real estate assets) to deal with larger amounts of debt, and usually have higher leverage ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Many theoretical studies and much empirical research have addressed these issues, but there is not yet a fully supported and unanimously accepted theory [5]. Indeed, what makes the capital structure debate so exciting is that only a few of the developed theories have been tested by empirical studies and the theories themselves lead to different, not mutually exclusive and sometimes opposed, results and conclusions.…”
Section: Introductionmentioning
confidence: 99%